A One‐Pot Synthesis of Symmetrical and Unsymmetrical Dipeptide Ureas. Issue 25 (30th July 2015) - Fayad, Antoine Abou; Pubill‐Ulldemolins, Cristina; Sharma, Sunil V.; Day, David; Goss, Rebecca J. M.
Abstract: We describe a flexible and high yielding synthesis of 1, 3‐disubstituted ureas that allows for the construction of both symmetrical and unsymmetrical dipeptide ureas, including easy access to 13 C‐labelled ureas, from amino acids and carbon dioxide at atmospheric pressure. Abstract : We describe a flexible and high yielding synthesis of 1, 3‐disubstituted ureas, that allows for the construction of both symmetrical and unsymmetrical dipeptide ureas, including easy access to 13 C labelled ureas, from amino acids and carbon dioxide at atmospheric pressure.